New Method for Load Flow Solution of Radial Distribution Networks - Kaur, Gurpreet (My University, 2009)
Distribution systems hold a very significant position in the power system since it is the main point of link between bulk power and consumers. The growing awareness of the consumers and the increasing competition in power sector has made it a must deal that the system should operate at its best possible conditions. This thesis presents a fast and efficient method for load-flow analysis of radial distribution networks. The proposed method is based on set theory and is fast. The proposed method handles any type of node numbering. The effectiveness of the method is shown by considering an example of 69- node radial distribution network and solving it for constant load, constant current, constant impedance, composite as well as exponential load modeling.
M.E. (Power Systems and Electric Drives)
Keywords: Load-flow; Radial Distribution Networks